2017
DOI: 10.1002/stc.2110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hysteretic properties of SMAs on seismic behavior of self-centering concentrically braced frames

Abstract: Summary Shape memory alloys (SMAs) exhibit nearly ideal superelastic properties when the ambient temperature is above the austenite finish temperature, which enables them to recover deformation and dissipate energy for the seismic‐resisting structures. This unique hysteretic properties of SMAs indicate they are very promising in developing self‐centering structures. As such, recent studies installed SMAs in concentrically braced frames (CBFs) to form SMA‐based self‐centering CBFs (SCCBFs) and illustrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, beam‐to‐column connections, base isolators, and bridges …”
Section: Introductionmentioning
confidence: 99%
“…The experimental results demonstrated that the dampers were effective in reducing both the peak and residual deformation of the structure subjected to strong earthquakes. Apart from damping systems, SMAs have also been considered in other seismic resistant devices and members, including braces, [14][15][16][17] beam-to-column connections, [18][19][20][21][22][23][24] base isolators, 25,26 and bridges. 27,28 Although the wire form of SMA has proven to be effective in providing energy dissipation and self-centring capability, there are still practical issues such as difficulty of gripping (especially when a large number of wires are to be included) and vulnerability to fracture at the gripping region due to local stress concentration.…”
Section: Introductionmentioning
confidence: 99%
“…SMA bracing systems have commonly been designed such that SMA elements are subjected to deformations within the superelastic strain limits of the SMA material. In numerical studies, it has been assumed that the SMA elements exhibit a linear strain hardening behavior when the strain in SMAs are over superelastic limit . Although this approach can be considered as a valid approach to evaluate the performance of buildings with SMA braces under seismic hazard levels considered in design codes, the ultimate state of SMA elements needs to be included in the modeling when the collapse performance of structures is assessed.…”
Section: Introductionmentioning
confidence: 99%
“…In numerical studies, it has been assumed that the SMA elements exhibit a linear strain hardening behavior when the strain in SMAs are over superelastic limit. 12,13,31,32 Although this approach can be considered as a valid approach to evaluate the performance of buildings with SMA braces under seismic hazard levels considered in design codes, the ultimate state of SMA elements needs to be included in the modeling when the collapse performance of structures is assessed. This paper investigates the effect of design parameters of SMA cable braces into the seismic and collapse performance of SMA-braced steel frame buildings.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method can be also used for design of structures by performing a series of designs and evaluations in an iterative manner that this iterative design approach causes a high computational cost and time . To achieve a predictable and desirable performance level without iteration in the design process, different performance‐based design methods such as direct displacement‐based design (DDBD) and performance‐based plastic design have been proposed. The aim of these design approaches is to achieve a target story drift under a specific level of seismic hazard.…”
Section: Introductionmentioning
confidence: 99%